The Role of Gratitude in Resolving Family Conflict: A Study of Tasawuf and Positive Psychology - Najwan Nafi'ah Nafi'ah; Akhmad Rofii Damyati; Sadrul Eslam Tahiri (Spiritualita, 2026)
Family conflict is a prevalent phenomenon that, if unmanaged, can disrupt household harmony and diminish the emotional well-being of family members. While previous research has extensively examined communication, adaptive strategies, and forgiveness in resolving family conflict, gratitude has seldom been positioned as a psychological and spiritual resource within an Islamic counseling framework, alongside its related concepts in Islamic psychology, namely patience (sabar) and trust in God (tawakal). The present study conceptually examines the role of gratitude in resolving family conflict and explores its connections with emotional regulation, empathy, and family communication, situated within the frameworks of positive psychology and Islamic perspectives. Employing a qualitative library research (conceptual) design, this study analyzes a body of literature—including journal articles, books, theses, and Islamic textual sources—on gratitude, family conflict, family resilience, and Islamic counseling, primarily published within the last fifteen years and selected through a structured search and thematic analysis. Data were collected through documentation and analyzed thematically by grouping the literature into conceptual themes, which were subsequently synthesized into an integrative conceptual model. The findings indicate that gratitude serves as a psychological and spiritual resource that enhances emotional regulation, fosters empathy, and promotes open, solution-oriented communication among family members. Within Islam, this role is further reinforced by gratitude’s close association with patience, trust in God, and forgiveness. Consequently, gratitude-based interventions may be integrated into Islamic family counseling practice, while also recognizing practical barriers that may impede their implementation.